The Correlation between Leukopenia and the Severity of Dengue Hemorrhagic Fever in Pediatric Patients - Mulyadi, Angelina; Sukmana, Judya; Anindya, Pramita; Purwoko, Suliman (Journal La Medihealtico, 2024)
The aim of this study is to investigate the correlation between leukopenia and the severity of DHF in pediatric patients treated at RSPAL dr. Ramelan Surabaya from January 2021 to December 2022. This analytical observational study employed a cross-sectional design, involving 126 patient records from RSPAL dr. Ramelan Surabaya during the specified period. The sample selection was done using purposive sampling. The variables under investigation were leukopenia on days 2 to 5 and the DHF grade in patients aged 5 to 14 years. The statistical correlation test, Kendall's tau-b, indicated that there is no significant correlation between leukopenia and the severity of DHF in pediatric patients, with a p-value of 0.340, meaning p > α (with α = 0.05). The data revealed that out of the patients, 88 (69.8%) had Grade I, 16 (12.7%) had Grade II, 19 (15.1%) had Grade III, and 3 (2.4%) had Grade IV. Leukopenia occurred in 49 (73.1%) Grade I patients, 9 (13.4%) Grade II patients, 7 (10.4%) Grade III patients, and 2 (3%) Grade IV patients. In conclusion, this study found no significant correlation between leukopenia and the severity of DHF in pediatric patients treated at RSPAL dr. Ramelan Surabaya from January 2021 to December 2022.